Risk of thromboembolism and fatal stroke in patients with psoriasis and nonvalvular atrial fibrillation: a Danish nationwide cohort study. (13th June 2014) - Ahlehoff, O.; Gislason, G.; Lamberts, M.; Folke, F.; Lindhardsen, J.; Larsen, C. T.; Torp‐Pedersen, C.; Hansen, P. R.
Abstract: Objectives: Psoriasis is a chronic inflammatory disease that is associated with a prothrombotic state and cardiovascular disease, including atrial fibrillation and thromboembolism. We therefore evaluated the impact of psoriasis in patients with atrial fibrillation and the performance of the CHA2 DS2 VASc score in these patients. Design, setting and participants: The study comprised all Danish patients hospitalized with nonvalvular atrial fibrillation in the period 1997–2011 ( n = 99 357). Follow‐up started 7 days from discharge and excluded subjects treated with anticoagulation. Poisson regression adjusted for CHA2 DS2 VASc score was used to estimate the incidence rate ratios and 95% confidence intervals. Main outcome measure: Hospitalization or death from thromboembolism. Results: Mean follow‐up was 3.5, 3.1, and 2.8 years for patients with no psoriasis, mild psoriasis and severe psoriasis, respectively. Patients with psoriasis were younger compared to patients without psoriasis, but CHA2DS2VASc score did not differ between the three groups. Thromboembolism rates per 100 patient‐years (95% confidence intervals) were 4.8 (4.7–4.9), 4.8 (4.2–5.4) and 6.1 (5.0–7.5) for patients with no psoriasis, mild psoriasis and severe psoriasis, respectively. Importantly, the observed thromboembolism rates in patients with severe psoriasis were markedly higher (2.6‐ to3.4‐fold) than predicted by the CHA2 DS2 VASc score. Relative to no psoriasis, incidence rate ratios were 0.99 (0.87–1.11) and 1.27 (1.02–1.57) for mild and severe psoriasis, respectively. Correspondingly, incidence rate ratios for fatal stroke were 0.97 (0.80–1.12) and 1.51 (1.12–2.05). Conclusions: In patients with nonvalvular atrial fibrillation not treated with oral anticoagulation, severe psoriasis was associated with increased risk of thromboembolism. In these patients, CHA2 DS2 VASc underestimated the risk of thromboembolism.